Composite material, preparation method thereof, isolating membrane, pole piece, battery and electric device
By using a composite material with a softening point of 5°C-60°C, cold press bonding between the isolation film and the electrode sheet is achieved, which solves the mold release problem caused by excessive hot press bonding and improves the cycling performance of the battery.
Patent Information
- Application Number
- CN202410020571.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2025-07-08
AI Technical Summary
The hot pressing bonding force between the isolation film and the electrode sheet in the existing batteries is too strong, resulting in the positive electrode sheet and/or the negative electrode sheet being easily deformed, reducing the battery circulation performance.
The composite materials, including acrylate polymers and dispersants, are used to control the softening point of Vika from 5℃-60℃, and there is no adhesion at room temperature. They penetrate into the pores of the electrode sheet and the isolation film through cold pressing process, achieving mechanical linkage and intermolecular force enhancement.
The cold pressing bonding force between the isolation film and the electrode sheet is improved, and the circulation performance of the battery is enhanced.
Smart Images

Figure CN120271942A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of batteries, and specifically relates to a composite material, a preparation method thereof, a separator, a pole piece, a battery, and an electric device. Background Art
[0002] Secondary batteries are not only applied to energy storage power systems such as hydraulic power plants, thermal power plants, wind power plants, and solar power plants, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, and electric vehicles, as well as in multiple fields such as military equipment and aerospace.
[0003] Currently, the binder of the separator in the battery uses polyvinylidene fluoride. Polyvinylidene fluoride is coated on the separator, wound with the pole piece, and then hot-pressed through heating to bond the pole piece and the separator, increasing the hardness of the battery core and maintaining the consistency of the battery core thickness. However, the adhesion force between the pole piece and the separator after hot pressing is too strong, resulting in the easy release of the positive pole piece and / or the negative pole piece during the cycling process of the battery, thereby reducing the cycling performance of the battery. Summary of the Invention
[0004] In view of the technical problems in the background art, this application provides a composite material, aiming to achieve cold pressing adhesion between the separator and the pole piece and improve the cycling performance of the battery.
[0005] To achieve the above object, this application provides a composite material in one aspect. The composite material includes: an acrylate polymer and a dispersant, and the Vicat softening point of the composite material is 5°C - 60°C.
[0006] Thus, when this composite material is used for the separator, at room temperature, the composite material has no adhesiveness under low pressure, which is convenient for the winding and unwinding of the separator. When the separator is wound with the positive and negative pole pieces and then undergoes a cold pressing process, the composite material can fully penetrate into the pores of the positive and negative pole pieces and the separator, enabling a strong mechanical interlocking effect between the composite material and the pole piece. At the same time, the intermolecular force between the composite material and the pole piece will also increase, realizing cold pressing adhesion between the composite material and the pole piece, and the adhesion force between the pole piece and the separator is appropriate, thereby improving the cycling performance of the battery.
[0007] In some embodiments of this application, the Vicat softening point of the composite material is 10°C - 50°C. Thus, the cycling performance of the battery can be improved.
[0008] In some embodiments of this application, the polymerization monomers of the acrylate polymer include a first monomer, a second monomer, and a third monomer.
[0009] The structure of the first monomer includes:
[0010]
[0011] Among them, R1 includes a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 18 carbon atoms, and R2 includes a hydrogen atom or an alkyl group having 1 to 18 carbon atoms which is substituted or unsubstituted by a hydroxyl group.
[0012] The structure of the second monomer includes:
[0013]
[0014] Among them, R3 and R4 each independently include a hydrogen atom, a phenyl group, or an alkyl group having 1 to 20 carbon atoms;
[0015] The structure of the third monomer includes:
[0016]
[0017] Among them, R5 includes a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and R6 includes a hydrogen atom, an alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, or an alkoxy group having 1 to 6 carbon atoms. Thus, the cold pressing adhesion force between the separator and the electrode can be improved.
[0018] In some embodiments of the present application, the first monomer includes at least one of ethyl acrylate, n-butyl acrylate, n-propyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isooctyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, acrylic acid, methacrylic acid, crotonic acid, or heptenoic acid. Thus, by using the above-mentioned first monomer, the Vicat softening point temperature of the composite material can be adjusted, the swelling resistance of the composite material can be improved, and the molecular interaction force between the composite material and the electrode can be improved.
[0019] In some embodiments of the present application, the second monomer includes at least one of styrene, pentene, hexene, heptene, octene, nonene, decene, dodecene, tridecene, tetradecene, pentadecene, or hexadecene. Thus, the cold pressing adhesion force between the separator and the negative electrode can be improved.
[0020] In some embodiments of the present application, the third monomer includes at least one of acrylamide, methacrylamide, N-methylolacrylamide, N-butylacrylamide, N-butoxymethylacrylamide, and N-(N-butoxymethyl)acrylamide. Thus, by using the above-mentioned third monomer, the molecular weight of the acrylate polymer can be adjusted and the molecular interaction force between the composite material and the electrode can be increased. Therefore, when the composite material is used for the separator, the cold pressing adhesion between the separator and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0021] In some embodiments of the present application, the mass ratio of the first monomer, the second monomer, and the third monomer is 100:(10 - 30):(1 - 20), and may be optionally 100:(15 - 25):(5 - 15). Thus, by controlling the first monomer, the second monomer, and the third monomer for preparing the acrylate polymer in the above mixing ratio, the Vicat softening point temperature of the acrylate polymer can be reduced, and the molecular interaction force between the composite material and the electrode can be increased. When the obtained composite material is used for the separator, under pressure at room temperature, the composite material can well infiltrate into the pores of the electrode and the separator, resulting in a strong mechanical interlocking effect between the composite material and the electrode. At the same time, the intermolecular interaction force between the composite material and the electrode will also be enhanced, thereby improving the cold pressing adhesion between the electrode and the separator.
[0022] In some embodiments of the present application, the mass ratio of the acrylate emulsion and the dispersant is 100:(1 - 15), and may be optionally 100:(5 - 12). Thus, when the composite material is used for the separator, the cold pressing adhesion between the separator and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0023] In some embodiments of the present application, the dispersant includes at least one of polyvinylpyrrolidone, polyacrylamide, sodium polystyrene sulfonate, polyacrylic acid, sodium polyacrylate, or sodium polymethacrylate. Thus, when the composite material is used for the separator, the cold pressing adhesion between the separator and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0024] In some embodiments of the present application, the number average molecular weight of the dispersant is 100 - 100000, and may be optionally 5000 - 80000. Thus, when the composite material is used for the separator, the cold pressing adhesion between the separator and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0025] In some embodiments of the present application, the composite material further includes a butadiene-based polymer, and the butadiene-based polymer includes at least one of polybutadiene, styrene / butadiene copolymer, acrylonitrile / butadiene copolymer, butadiene / isoprene copolymer, or butadiene / propylene copolymer. Thus, when the composite material is used for the separator membrane, the cold pressing adhesion between the separator membrane and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0026] In some embodiments of the present application, the mass ratio of the acrylate polymer, the dispersant, and the butadiene-based polymer is 100:(1 - 15):(1 - 100), and may be optionally 100:(5 - 12):(5 - 50). Thus, when the composite material is used for the separator membrane, the cold pressing adhesion between the separator membrane and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0027] In some embodiments of the present application, the glass transition temperature of the butadiene-based polymer is less than or equal to 20°C, and may be optionally less than or equal to 15°C. Thus, when the composite material is used for the separator membrane, the cold pressing adhesion between the separator membrane and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0028] In some embodiments of the present application, the Dv50 of the butadiene-based polymer is 100 nm - 300 nm, and may be optionally 150 nm - 250 nm. Thus, when the composite material is used for the separator membrane, the cold pressing adhesion between the separator membrane and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0029] In some embodiments of the present application, the viscosity of the butadiene-based polymer at 25°C is 10 mPa·s - 300 mPa·s, and may be optionally 80 mPa·s - 200 mPa·s. Thus, when the composite material is used for the separator membrane, the cold pressing adhesion between the separator membrane and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0030] In some embodiments of the present application, the volume average particle size Dv50 of the composite material is 2 μm - 20 μm, and may be optionally 5 μm - 15 μm. Thus, when the composite material is used on the separator membrane, it can prevent the composite material from clogging the pores of the separator membrane, improve the passage of active ions through the separator membrane, and solve the problem that a relatively thick coating formed by coating the composite material on the separator membrane affects the low energy density of the battery prepared later.
[0031] The second aspect of the present application provides a method for preparing the above composite material, including: mixing the acrylate polymer and the dispersant to obtain a composite material, and the Vicat softening point of the composite material is 5°C - 60°C.
[0032] Thus, by using this method, the above-mentioned composite material with excellent cold pressing adhesiveness can be prepared. When this composite material is used for a separator, the cold pressing adhesion between the separator and the electrode can be improved, and the cycle performance of the battery can be enhanced.
[0033] In the third aspect of this application, a separator is provided. The separator includes the above-mentioned composite material or the composite material obtained by the above method. Thus, cold pressing adhesion between the separator and the electrode can be achieved, and the adhesiveness between the separator and the electrode is appropriate, thereby improving the cycle performance of the battery.
[0034] In the fourth aspect of this application, an electrode is provided. The electrode includes the above-mentioned composite material or the composite material obtained by the above method. Thus, cold pressing adhesion between the separator and the electrode can be achieved, and the adhesiveness between the separator and the electrode is appropriate, thereby improving the cycle performance of the battery.
[0035] In the fifth aspect of this application, a battery is provided. The battery includes the above-mentioned separator and / or the above-mentioned electrode. Thus, the battery has excellent cycle performance.
[0036] In the sixth aspect of this application, an electrical device is provided. The electrical device includes the above-mentioned battery. Thus, the electrical device has excellent cycle performance.
[0037] The additional aspects and advantages of this application will be partially given in the following description, partially will become apparent from the following description, or be understood through the practice of this application. Description of the Drawings
[0038] By reading the following detailed description of the optional embodiments, various other advantages and benefits will become clear to those of ordinary skill in the art. The drawings are only for the purpose of showing the optional embodiments and are not considered to be a limitation of this application. Moreover, in all the drawings, the same reference numerals are used to represent the same components. In the drawings:
[0039] Figure 1 is a schematic diagram of a battery according to an embodiment of this application.
[0040] Figure 2 is Figure 1 an exploded view of the battery according to an embodiment of this application shown in
[0041] Figure 3 is a schematic diagram of a battery module according to an embodiment of this application.
[0042] Figure 4 is a schematic diagram of a battery pack according to an embodiment of this application.
[0043] Figure 5 is Figure 4Exploded view of a battery pack according to an embodiment of the present application as shown.
[0044] Figure 6 It is a schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.
[0045] Description of reference numerals:
[0046] 1 Battery cell; 11 Housing; 12 Electrode assembly; 13 Cover plate; 2 Battery module; 3 Battery pack; 31 Upper box body; 32 Lower box body. Detailed implementation manners
[0047] The embodiments of the technical solutions of the present application will be described in detail below. The following embodiments are only used to more clearly illustrate the technical solutions of the present application, so they are only examples and cannot be used to limit the protection scope of the present application.
[0048] Referring to "embodiments" herein means that the specific features, structures or characteristics described in connection with the embodiments may be included in at least one embodiment of the present application. The phrase appears at various positions in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art explicitly and implicitly understand that the embodiments described herein may be combined with other embodiments.
[0049] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The ranges defined in this way can include the end values or not include the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 - 120 and 80 - 110 are listed for a particular parameter, ranges of 60 - 110 and 80 - 120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, then the following ranges are all contemplated: 1 - 3, 1 - 4, 1 - 5, 2 - 3, 2 - 4 and 2 - 5. In the present application, unless otherwise stated, the numerical range "a - b" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0 - 5" means that all real numbers between "0 - 5" have been fully listed herein, and "0 - 5" is only an abbreviated representation of these numerical combinations. Additionally, when stating that a certain parameter is an integer ≥2, it is equivalent to disclosing that the parameter is, for example, the integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0050] If there is no special instruction, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions.
[0051] Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all steps of the present application can be carried out sequentially or randomly, and are preferably carried out sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) carried out sequentially, or may include steps (b) and (a) carried out sequentially. For example, it is mentioned that the method may further include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0053] Unless otherwise specified, the terms "comprising" and "including" mentioned in the present application mean open-ended or may be closed-ended. For example, the "comprising" and "including" may mean that other components not listed may also be included or contained, or may only include or contain the components listed.
[0054] Unless otherwise specified, in the present application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) while B is true (or exists); or both A and B are true (or exist).
[0055] Currently, from the perspective of the development of the market situation, the application of secondary batteries is becoming more and more widespread. Secondary batteries are not only used in energy storage power systems such as hydraulic, thermal, wind and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles and electric cars, as well as in many fields such as military equipment and aerospace. With the continuous expansion of the application fields of secondary batteries, the market demand is also continuously increasing.
[0056] The battery cell includes a positive electrode plate, a negative electrode plate and a separator. The battery cell has a certain hardness. That is, since the bonded positive and negative electrode plates and the separator are attached to each other and support each other, a structure with a certain thickness is formed, and the structure with a certain thickness has a certain hardness. The negative electrode will expand during charge and discharge. If the bonding force is weak, gaps will be formed between the positive and negative electrode plates and the separator, and the positive and negative electrode plates and the separator cannot be attached to each other and support each other, resulting in the battery cell becoming loose and the hardness decreasing. At this time, the cycle performance of the battery deteriorates, directly leading to a shortened battery life, and electric vehicles need to frequently replace the battery, increasing the cost for consumers of electric vehicles.
[0057] The separator film adheres tightly to the electrode sheet, which can improve the discharge capacity of the battery, reduce the internal resistance, reduce the polarization loss, extend the cycle life of the battery, and improve the utilization rate of the secondary battery. The commonly used binder on the existing separator film is polyvinylidene fluoride, which requires a hot pressing process (heating is accompanied during the pressing process after stacking the separator film and the electrode sheet) to make the separator film adhere tightly to the electrode sheet.
[0058] The composite material of the present application includes an acrylate polymer and a dispersant. The addition of the dispersant can not only adjust the Vicat softening point of the composite material, but also facilitate the granulation of the composite material, and control the Vicat softening point of the composite material to be 5°C - 60°C. When this composite material is used for the separator film, at room temperature, the composite material has no adhesiveness under low pressure, which is convenient for the winding and unwinding of the separator film. When the separator film undergoes a cold pressing process (heating is not performed during the pressing process after stacking the separator film and the electrode sheet) after being wound with the positive and negative electrode sheets, the composite material can fully penetrate into the pores of the positive and negative electrode sheets and the separator film, enabling a strong mechanical interlocking effect to occur between the composite material and the electrode sheet. At the same time, the intermolecular force between the composite material and the electrode sheet will also increase, realizing cold pressing adhesion between the composite material and the electrode sheet, and the adhesive force between the electrode sheet and the separator film is appropriate, thereby improving the cycle performance of the battery.
[0059] The composite material disclosed in the embodiments of the present application is applicable to batteries, and the batteries disclosed in the embodiments of the present application can be used in electrical devices that use the battery as a power source or various energy storage systems that use the battery as an energy storage element. The electrical devices can include, but are not limited to, mobile phones, tablets, laptop computers, electric toys, power tools, battery cars, electric vehicles, ships, spacecraft, and the like. Among them, the electric toys can include fixed or mobile electric toys, such as game consoles, electric vehicle toys, electric ship toys, and electric aircraft toys, etc. The spacecraft can include airplanes, rockets, space shuttles, and spaceships, etc.
[0060] The first aspect of the present application provides a composite material, the composite material includes: an acrylate polymer and a dispersant, and the Vicat softening point of the composite material is 5°C - 60°C.
[0061] In this application, the Vicat softening point refers to the temperature at which the material begins to soften and loses its original strength and stiffness. The higher the Vicat softening point, the better the dimensional stability of the material when heated, the smaller the thermal deformation, that is, the better the heat-resistant deformation ability and the greater the rigidity; the lower the Vicat softening point, the more easily the ambient temperature exceeds the Vicat softening point of the material, the greater the thermal deformation ability of the material, and it is easy to soften. And the measurement of the Vicat softening point can be carried out by using the instruments and methods well-known in the art. For example, it can be determined according to ISO306:2013 Determination of Vicat softening temperature of thermoplastics, and test method A50 is selected. The equipment selects the WKT-VST300 type thermo-deformation softening point temperature measuring instrument of Jaisen Company for testing, with a load of 10 N, a heating rate of 50 °C / h, and a sample thickness of 5 mm.
[0062] When the Vicat softening point of the composite material is higher, the composite material still has a certain strength and stiffness, and the dimensional stability of the composite material is better. When cold pressing, it is not easy to penetrate into the pores of the electrode sheet and the separator film, so the mechanical interlocking effect and the intermolecular force will be weakened, affecting the cold pressing adhesion; when the Vicat softening point of the composite material is lower, the composite material is more likely to deform and soften, and can more easily penetrate into the pores of the electrode sheet and the separator film during cold pressing, improving the mechanical interlocking effect and the intermolecular force, thereby realizing the cold pressing adhesion between the electrode sheet and the separator film.
[0063] The composite material of this application includes an acrylate polymer and a dispersant. The addition of the dispersant can not only adjust the Vicat softening point of the composite material, but also facilitate the granulation of the composite material, and control the Vicat softening point of the composite material to be 5 °C - 60 °C. When this composite material is used for the separator film, after winding with the positive and negative electrode sheets and performing the cold pressing process, the composite material can well penetrate into the pores of the electrode sheet and the separator film, causing a strong mechanical interlocking effect between the composite material and the electrode sheet. At the same time, the intermolecular force between the composite material and the electrode sheet will also increase, thereby realizing the cold pressing adhesion between the separator film and the electrode sheet, and at the same time, the adhesion between the electrode sheet and the separator film is appropriate, so that the cycle performance of the battery can be improved.
[0064] In some embodiments of the present application, the Vicat softening point of the composite material is 5°C - 60°C, such as 7°C - 58°C, 10°C - 55°C, 12°C - 53°C, 15°C - 50°C, 20°C - 45°C, 25°C - 40°C, 30°C - 35°C, etc. In some other embodiments of the present application, the Vicat softening point of the composite material is 10°C - 50°C. Thus, when the Vicat softening point of the composite material of the present application meets the above conditions, when the composite material is used for the separator membrane, after winding with the positive and negative electrode plates and then performing the cold pressing process, the composite material can well penetrate into the pores of the electrode plates and the separator membrane, enabling a strong mechanical interlocking effect between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby realizing the cold pressing adhesion between the separator membrane and the electrode plates, and the adhesion force between the electrode plates and the separator membrane is appropriate, so as to improve the cycle performance of the battery.
[0065] In some embodiments of the present application, the acrylate polymer polymerization monomers include a first monomer, a second monomer, and a third monomer.
[0066] The structure of the first monomer includes:
[0067]
[0068] Wherein, R1 includes a hydrogen atom, a hydroxyl group, or an alkyl group with 1 - 18 carbon atoms, and R2 includes a hydrogen atom or an alkyl group with 1 - 18 carbon atoms that is substituted or unsubstituted by a hydroxyl group.
[0069] The structure of the second monomer includes:
[0070]
[0071] Wherein, R3 and R4 each independently include a hydrogen atom, a phenyl group, or an alkyl group with 1 - 20 carbon atoms;
[0072] The structure of the third monomer includes:
[0073]
[0074] Wherein, R5 includes a hydrogen atom or an alkyl group with 1 - 6 carbon atoms, and R6 includes a hydrogen atom, an alkyl group with 1 - 6 carbon atoms substituted by a hydroxyl group, or an alkoxy group with 1 - 6 carbon atoms.
[0075] The polymerization monomers of the acrylate polymer include the above-mentioned first monomer, second monomer and third monomer. The first monomer includes an unsaturated ester group, a carboxyl group or a hydroxy ester group. The second monomer includes an alkenyl group. The structure of the third monomer includes an unsaturated amide group. By polymerizing the first monomer, second monomer and third monomer to prepare the acrylate polymer, the adhesiveness of the acrylate polymer can be improved. At the same time, the unsaturated ester group, carboxyl group or hydroxy ester group contained in the first monomer can form a binding force with the functional groups on the pole piece and the separator material, improving the bonding effect between the pole piece and the separator.
[0076] In some embodiments of the present application, the structure of the first monomer includes:
[0077]
[0078] Among them, R1 includes a hydrogen atom, a hydroxyl group or an alkyl group with 1-18 carbon atoms. R2 includes a hydrogen atom or an alkyl group with 1-18 carbon atoms that is substituted or unsubstituted by a hydroxyl group. The first monomer includes an unsaturated ester group, a carboxyl group or a hydroxy ester group, which is beneficial to the polymerization of the monomer, and at the same time improves the molecular interaction force between the composite material and the pole piece. And as a flexible monomer segment in the molecular chain segment, it can adjust the Vicat softening point of the composite material, thereby helping to adjust the Vicat softening point of the composite material within a suitable range.
[0079] As an example, the alkyl group with 1-18 carbon atoms can be understood as an alkyl group with 1-18 carbon atoms, such as methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), tert-butyl (-C(CH3)3), n-pentyl (-CH2CH2CH2CH2CH3), n-hexyl (-CH2CH2CH2CH2CH2CH3), etc.
[0080] As an example, the alkyl group with 1-18 carbon atoms substituted by a hydroxyl group can be understood as at least one hydrogen atom in the alkyl group with 1-18 carbon atoms being substituted by a hydroxyl group, such as -CH2OH, -CH2CH2OH, -CH2CH2CH2OH, -CH(CH2OH)2, -CH2CH2CH2CH2OH, -C(CH2OH)3, -CH2CH2CH2CH2CH2OH, etc.
[0081] In some embodiments of the present application, the first monomer includes at least one of ethyl acrylate, n-butyl acrylate, n-propyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isooctyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, acrylic acid, methacrylic acid, crotonic acid or heptenoic acid. Thus, by using the above-mentioned first monomer of the present application, not only can the molecular interaction force between the composite material and the electrode be improved, but also the Vicat softening point of the composite material can be adjusted.
[0082] In some embodiments of the present application, the structure of the second monomer includes:
[0083]
[0084] Wherein, R3 includes a hydrogen atom or an alkyl group with 1-6 carbon atoms, and R4 includes a hydrogen atom, a phenyl group or an alkyl group with 1-20 carbon atoms. Thus, the second monomer contains an unsaturated double bond, which is beneficial to the polymerization of the monomer and can improve the adhesion between the separator and the negative electrode.
[0085] It should be noted that the alkyl group with 1-20 carbon atoms can be understood as an alkyl group with 1-20 carbon atoms, such as methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), tert-butyl (-C(CH3)3), n-pentyl (-CH2CH2CH2CH2CH3), n-hexyl (-CH2CH2CH2CH2CH2CH3), etc.
[0086] In some embodiments of the present application, the second monomer includes at least one of styrene, pentene, hexene, heptene, octene, nonene, decene, dodecene, tridecene, tetradecene, pentadecene, hexadecene. Thus, by using the above-mentioned second monomer of the present application, the adhesion performance between the composite material and the electrode can be adjusted.
[0087] In some embodiments of the present application, the structure of the third monomer includes:
[0088]
[0089] Among them, R4 includes a hydrogen atom or an alkyl group with 1 to 6 carbon atoms, and R5 includes a hydrogen atom, a hydroxyl-substituted alkyl group with 1 to 6 carbon atoms, or an alkoxy group with 1 to 6 carbon atoms. Thus, the structure of the third monomer includes an unsaturated amide group, which not only facilitates the polymerization of the monomer but also can increase the intermolecular force between the electrode sheet and the composite material, thereby improving the cold pressing adhesiveness between the composite material and the electrode sheet.
[0090] It should be noted that the hydroxyl-substituted alkyl group with 1 to 6 carbon atoms can be understood as a group in which at least one hydrogen atom on the alkyl group with 1 to 6 carbon atoms is substituted by a hydroxyl group, such as -CH2OH, -CH2CH2OH, -CH2CH2CH2OH, -CH(CH2OH)2, -CH2CH2CH2CH2OH, -C(CH2OH)3, -CH2CH2CH2CH2CH2OH, etc. At the same time, the hydroxyl-substituted alkoxy group with 1 to 6 carbon atoms can be understood as a group in which at least one hydrogen atom on the alkoxy group with 1 to 6 carbon atoms is substituted by a hydroxyl group, such as methoxy (HOCH2O-), ethoxy (OHCH2CH2O-), propoxy (OHCH2CH2CH2O-), etc.
[0091] In some embodiments of the present application, the third monomer includes at least one of acrylamide, methacrylamide, N-hydroxymethylacrylamide, N-butylacrylamide, N-butoxymethylacrylamide, and N-(N-butoxymethyl)acrylamide. Thus, by using the above-mentioned third monomer, not only can the molecular weight of the composite material be adjusted, but also the intermolecular force between the electrode sheet and the composite material can be increased, thereby improving the cold pressing adhesiveness between the composite material and the electrode sheet.
[0092] In some embodiments of the present application, in the polymerization monomers of the acrylate polymer, the mass ratio of the first monomer, the second monomer and the third monomer is 100:(10 - 30):(1 - 20), for example, 100:(12 - 28):(1 - 20), 100:(15 - 25):(1 - 20), 100:(17 - 22):(1 - 20), 100:(18 - 20):(1 - 20), 100:(10 - 30):(5 - 15), 100:(10 - 30):(7 - 12), 100:(10 - 30):(8 - 10), etc. Thus, by controlling the mixing ratio of the first monomer, the second monomer and the third monomer for preparing the acrylate polymer within the above range, the obtained acrylate polymer has relatively high adhesiveness. Then, when the obtained acrylate polymer is mixed with a dispersant, the obtained composite material has a relatively low Vicat softening point. When this composite material is used for a separator membrane, at room temperature, the composite material has no adhesiveness under a relatively low pressure, which is convenient for the winding and unwinding of the separator membrane. When the separator membrane is wound with the positive and negative electrode plates and then undergoes a cold pressing process, the composite material can fully penetrate into the pores of the positive and negative electrode plates and the separator membrane, resulting in a strong mechanical interlocking effect between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby realizing the cold pressing adhesion between the composite material and the electrode plates, and the adhesion between the electrode plates and the separator membrane is appropriate, so as to improve the cycle performance of the battery. In some other embodiments of the present application, in the polymerization monomers of the acrylate composite material, the mass ratio of the first monomer, the second monomer and the third monomer is 100:(15 - 25):(5 - 15).
[0093] In some embodiments of the present application, the dispersant includes at least one of polyvinylpyrrolidone, polyacrylamide, sodium polystyrene sulfonate, polyacrylic acid, sodium polyacrylate, and sodium polymethacrylate. Adding the dispersant with the above composition to the composite material of the present application not only has good dispersion performance for the suspension system of the acrylate polymer, reducing the random aggregation of the emulsion system, but also can adjust the Vicat softening point of the composite material and is beneficial to the granulation of the composite material. When this composite material is used for a separator membrane, at room temperature, the composite material has no adhesiveness under a relatively low pressure, which is convenient for the winding and unwinding of the separator membrane. When the separator membrane is wound with the positive and negative electrode plates and then undergoes a cold pressing process, the composite material can fully penetrate into the pores of the positive and negative electrode plates and the separator membrane, resulting in a strong mechanical interlocking effect between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby realizing the cold pressing adhesion between the composite material and the electrode plates, and the adhesion between the electrode plates and the separator membrane is appropriate, so as to improve the cycle performance of the battery.
[0094] In some embodiments of the present application, the mass ratio of the acrylate polymer to the dispersant is 100:(1-15), such as 100:(2-14), 100:(3-13), 100:(4-12), 100:(5-11), 100:(6-10), 100:(7-9), 100:(7-8), etc. Thus, by adding the dispersant in the above content to the composite material of the present application, it not only has good dispersion performance for the suspension system of the acrylate polymer, reduces the random aggregation of the emulsion system, but also can adjust the Vicat softening point of the composite material, and is beneficial to the granulation of the composite material. When the composite material is used for the separator film, at room temperature, the composite material has no adhesiveness under a low pressure, which is convenient for the winding and unwinding of the separator film. When the separator film is cold-pressed after being wound with the positive and negative electrode plates, the composite material can fully penetrate into the pores of the positive and negative electrode plates and the separator film, so that a strong mechanical interlocking effect occurs between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby realizing the cold-pressing adhesion between the composite material and the electrode plates, and the adhesion between the electrode plates and the separator film is appropriate, so that the cycle performance of the battery can be improved. In some further embodiments of the present application, the mass ratio of the acrylate composite material to the dispersant is 100:(5-12).
[0095] In some embodiments of the present application, the number-average molecular weight of the dispersant is 100-100000, such as 500-100000, 3000-100000, 5000-100000, 8000-100000, 10000-100000, 30000-90000, 50000-70000, 50000-60000, 55000-60000, etc. Thus, by adding the dispersant with the above molecular weight to the composite material of the present application, it can not only reduce the random aggregation of the emulsion system of the acrylate polymer, but also can adjust the Vicat softening point of the composite material, and is beneficial to the granulation of the composite material. When the composite material is used for the separator film, it can improve the cold-pressing adhesion between the separator film and the electrode plate and improve the cycle performance of the battery. In some embodiments of the present application, the number-average molecular weight of the dispersant is 5000-80000.
[0096] In this application, the number-average molecular weight of the dispersant can be determined with reference to the gel permeation chromatography method in Standard GB / T 21863-2008. Specifically, in this application, it can be carried out in the following manner: Use an ultra-high performance polymer chromatograph: ACQUITY APC; detector: ACQUITY refractive index detector. Standard: polystyrene set; running time: 30 min; detector: ACQUITY refractive index (RI) detector; column oven temperature: 90 °C; detector temperature: 55 °C. Sample test: a. Standard sample and test sample preparation: Weigh 0.002 g to 0.004 g of the standard sample / test sample respectively and add 2 mL of mobile phase liquid to prepare a mixed standard of 0.1% to 0.5%, and place it in the refrigerator for > 8 h; b. Standard solution / sample test: Edit the sample group to be measured, select the established sample group method, and click the run queue to start testing the sample after the baseline is stable; (4) Data processing: According to the relationship between the retention time and the molecular weight, use the chemical workstation to establish a calibration curve, integrate and quantify the sample spectrum, and the chemical workstation automatically generates the molecular weight and molecular weight distribution results.
[0097] In some embodiments of this application, the composite material further includes a butadiene-based polymer, and the butadiene-based polymer includes at least one of polybutadiene, styrene / butadiene copolymer, acrylonitrile / butadiene copolymer, butadiene / isoprene copolymer, or butadiene / propylene copolymer. Thus, by adding the butadiene-based polymer with the above composition to the composite material in this application, not only can the Vicat softening point of the composite material be further adjusted, but also an integrated composite material after mixing can be obtained. Since the composite material contains a butadiene-based composite material, which is the same type of substance as the SBR (styrene-butadiene rubber) binder enriched on the surface of the negative electrode, the adhesion between the composite material and the negative electrode sheet can be further improved.
[0098] In some embodiments of the present application, the mass ratio of the acrylate polymer, the dispersant, and the butadiene polymer is 100:(1 - 15):(1 - 100), such as 100:(2 - 13):(1 - 100), 100:(5 - 10):(1 - 100), 100:(8 - 10):(1 - 100), 100:(1 - 15):(5 - 95), 100:(1 - 15):(10 - 90), 100:(1 - 15):(20 - 80), 100:(1 - 15):(30 - 70), 100:(1 - 15):(40 - 60), 100:(1 - 15):(50 - 55), etc. Thus, by mixing the acrylate composite material, the dispersant, and the butadiene composite material in the above ratios in the present application, not only can the random agglomeration of the acrylate polymer emulsion system be reduced, which is beneficial to the dispersion of acrylate polymer particles, but also the Vicat softening point of the composite material can be adjusted. The obtained composite material has a lower Vicat softening point. When this composite material is used for the separator film, at room temperature, the composite material has no adhesiveness under a lower pressure, which is convenient for the winding and unwinding of the separator film. When the separator film is wound with the positive and negative electrode plates and then undergoes a cold pressing process, the composite material can fully penetrate into the pores of the positive and negative electrode plates and the separator film, resulting in a strong mechanical interlocking effect between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby realizing the cold pressing adhesion between the composite material and the electrode plates, and the adhesion between the electrode plates and the separator film is appropriate, so that the cycle performance of the battery can be improved. In some other embodiments of the present application, the mass ratio of the acrylate polymer, the dispersant, and the butadiene polymer is 100:(5 - 12):(5 - 50).
[0099] In some embodiments of the present application, the glass transition temperature of the butadiene polymer is less than or equal to 20°C. Thus, by adding the butadiene polymer with this glass transition temperature to the composite material in the present application, the Vicat softening point of the composite material can be reduced. When this composite material is used for the separator film, at room temperature, the composite material has no adhesiveness under a lower pressure, which is convenient for the winding and unwinding of the separator film. When the separator film is wound with the positive and negative electrode plates and then undergoes a cold pressing process, the composite material can fully penetrate into the pores of the positive and negative electrode plates and the separator film, resulting in a strong mechanical interlocking effect between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby realizing the cold pressing adhesion between the composite material and the electrode plates, and the adhesion between the electrode plates and the separator film is appropriate, so that the cycle performance of the battery can be improved.
[0100] It should be noted that the glass transition temperature is the temperature at which a polymer changes from a high elastic state to a glassy state. It refers to the transition temperature of an amorphous polymer (including the non-crystalline part of a crystalline polymer) from a glassy state to a high elastic state or vice versa. It is the lowest temperature at which the macromolecular segments of an amorphous polymer can move freely, usually denoted as Tg. Above the glass transition temperature, the polymer exhibits elasticity; below the glass transition temperature, the polymer exhibits brittleness. The glass transition temperature can be measured by methods commonly used in the art. For example, it can be tested by differential scanning calorimetry with reference to GB / T 19466.2.
[0101] In some embodiments of the present application, the Dv50 of the butadiene-based polymer is 100 nm - 300 nm, such as 150 nm - 250 nm, 150 nm - 200 nm, etc. Thus, when this composite material is used for the separator membrane, the cold pressing adhesion between the separator membrane and the electrode can be improved, and the hardness of the battery cell and the cycling performance of the battery can be enhanced. In some embodiments of the present application, the Dv50 of the butadiene-based polymer is 150 nm - 250 nm.
[0102] It should be noted that in the embodiments of the present application, the Dv50 of the butadiene-based polymer is the particle size corresponding to when the cumulative particle size volume distribution percentage reaches 50%. The test method is as follows:
[0103] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Laser diffraction method for particle size distribution. Use a laser particle size analyzer (Malvern 3000, MasterSizer 3000) for testing, and use a helium-neon red light source for the main light source. Take a clean small beaker, add 1 g of the sample to be tested, add one drop of surfactant, add 20 ml of deionized water (the sample concentration ensures a light obscuration of 8 - 12%), and ultrasonicate for 5 min at 53 KHz / 120 W to ensure complete dispersion of the sample. Turn on the laser particle size analyzer, clean the optical path system, and then automatically test the background. Stir the ultrasonified sample solution to make it evenly dispersed, place it in the sample cell as required, and start measuring the particle size. The measurement result can be read from the instrument.
[0104] In some embodiments of the present application, the viscosity of the butadiene-based polymer at 25 °C is 10 mPa·s - 300 mPa·s, such as 50 mPa·s - 250 mPa·s, 100 mPa·s - 200 mPa·s, 150 mPa·s - 220 mPa·s, etc. Thus, by using the butadiene-based polymer within this viscosity range in the present application, the butadiene-based polymer has good compatibility with the acrylate-based polymer, so that the composite material system is uniformly dispersed, realizing the cold pressing adhesion between the composite material and the electrode sheet, and the adhesion force between the electrode sheet and the separator is appropriate, thereby improving the cycle performance of the battery. In some other embodiments of the present application, the viscosity of the butadiene-based polymer at 25 °C is 80 mPa·s - 200 mPa·s.
[0105] It should be noted that in the embodiments of the present application, the viscosity test method of the butadiene-based polymer at 25 °C adopts the national standard: GB / T 10247-2008 "Viscosity Measurement Method". Specifically, at 25 °C, a rotary Brookfield viscometer is used. When the 62# rotor rotates continuously at a constant speed in the sample, the shear force causes the spring to generate torque, and the torque is proportional to the viscosity, so as to obtain the viscosity value.
[0106] In some embodiments of the present application, the volume particle size distribution Dv50 of the composite material is 2 μm - 20 μm, such as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc. When the composite material satisfying the above volume average particle size Dv50 is used for the separator in the present application, it can not only reduce the risk of the composite material clogging the pores of the separator, but also improve the problem that the composite material is coated on the separator to form a relatively thick coating, which affects the energy density of the battery prepared later. In some other embodiments of the present application, the volume particle size distribution Dv50 of the composite material is 5 μm - 15 μm.
[0107] It should be noted that in the embodiments of the present application, the volume average particle size Dv50 of the composite material is the particle size corresponding to when the cumulative particle size volume distribution percentage reaches 50%, and the test method is as follows:
[0108] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Laser diffraction method for particle size distribution. Test using a laser particle size analyzer (Malvern 3000, MasterSizer 3000), and use a helium-neon red light source as the main light source. Take a clean small beaker, add 1 g of the sample to be tested, add one drop of surfactant, add 20 ml of deionized water (ensure the light obscuration of the sample concentration is 8-12%), and ultrasonicate for 5 min at 53 KHz / 120 W to ensure complete dispersion of the sample. Turn on the laser particle size analyzer, clean the optical path system, and then automatically test the background. Stir the ultrasonified sample solution to make it evenly dispersed, place it in the sample cell as required, and start measuring the particle size. The measurement results can be read from the instrument.
[0109] In the second aspect of the present application, a method for preparing the above composite material is proposed, including: mixing an acrylate polymer with a dispersant to obtain a composite material, and the Vicat softening point of the composite material is 5°C - 60°C.
[0110] In some embodiments of the present invention, the method for preparing the composite material described above may adopt the following steps:
[0111] Blend water, an emulsifier, an initiator, a first monomer, a second monomer, and a third monomer, and heat and react to obtain an acrylate emulsion;
[0112] Blend the acrylate emulsion and the dispersant to obtain a composite material.
[0113] The acrylate emulsion is prepared by emulsion polymerization using a first monomer, a second monomer, and a third monomer. The acrylate composite material prepared using the above monomers has high adhesiveness. The composite material obtained by combining it with a dispersant has an appropriate Vicat softening point. When this composite material is used for the separator film, at room temperature, the composite material has no adhesiveness under low pressure, which is convenient for the winding and unwinding of the separator film. When the separator film undergoes a cold pressing process after being wound with the positive and negative electrode plates, the composite material can fully penetrate into the pores of the positive and negative electrode plates and the separator film, enabling a strong mechanical interlocking effect between the composite material and the electrode plates. At the same time, the intermolecular force between the composite material and the electrode plates will also increase, thereby achieving cold pressing adhesion between the composite material and the electrode plates, and the adhesion between the electrode plates and the separator film is appropriate, thus improving the cycle performance of the battery.
[0114] In the present application, an acrylic emulsion is obtained through emulsion polymerization, and then the acrylate emulsion and the dispersant are mixed and the composite material is obtained through spray drying.
[0115] Emulsion polymerization: Emulsion polymerization is that monomers are dispersed in water to form an emulsion by means of an emulsifier and mechanical stirring, and then an initiator is added to initiate the polymerization of the monomers.
[0116] Emulsifier. An emulsifier is a substance that can transform immiscible oil and water into an emulsion that is difficult to layer. Emulsifiers are usually surfactants with both hydrophilic polar groups and hydrophobic (lipophilic) non-polar groups. For example, the emulsifier includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium dodecylbenzenesulfate, sodium laurate, sodium stearate, or sodium palmitate.
[0117] Initiator. An initiator is a substance that can initiate the polymerization reaction of monomers. For example, a radical initiator refers to a class of compounds that are easily decomposed by heat into free radicals (i.e., primary free radicals) and can be used to initiate the radical polymerization and copolymerization reactions of vinyl and diene monomers. For example, the initiator includes at least one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, dimethyl azobisisobutyrate, benzoyl peroxide, or di-n-octanoyl peroxide.
[0118] Water, emulsifier, initiator, and the constituent monomers of the acrylate polymer are blended and stirred. After the water and emulsifier are stirred and dispersed, an emulsion is formed, that is, the emulsifier forms micelles in the aqueous phase, and most of the micelles solubilize the monomers. Under heating conditions, the initiator initiates the polymerization of the monomers inside the micelles to obtain an emulsion.
[0119] Spray drying. Through mechanical action, the material to be dried (a mixture of acrylate polymer emulsion and dispersant) is dispersed into very fine particles like fog, contacts with hot air (increasing the water evaporation area and accelerating the drying process), and most of the water is removed instantaneously, drying the solid matter in the material into powder.
[0120] In some embodiments of the present application, the above method further includes: during the mixing of the acrylate emulsion and the dispersant, a butadiene polymer is also added. Specifically, during the mixing of the acrylate emulsion and the dispersant in the present application, the dispersant has good dispersion performance for the suspension system, reducing the random aggregation of the emulsion system. And adding a butadiene copolymer during the mixing of the acrylate emulsion and the dispersant can adjust the Vicat softening point of the composite material. When this composite material is used for the separator membrane, it can improve the cold pressing adhesion between the separator membrane and the electrode sheet and improve the cycling performance of the battery.
[0121] The third aspect of the present application proposes a separator membrane, including the composite material of the first aspect of the present application or the composite material obtained by the method of the second aspect of the present application. Thus, when the above composite material of the present application is applied to the separator membrane, it can improve the cold pressing adhesion between the separator membrane and the electrode sheet and improve the hardness of the battery cell and the cycling performance of the battery.
[0122] In some embodiments of the present application, the separator membrane of the present application includes a base film and an adhesive layer, the adhesive layer is formed on at least one side of the base film, and the adhesive layer includes the composite material of the first aspect of the present application or the composite material obtained by the method of the second aspect of the present application. For example, adhesive layers are formed on both opposite sides of the base film.
[0123] There is no particular limitation on the type of the base film in the present application, and any well-known base film with a porous structure having good chemical stability and mechanical stability can be selected.
[0124] In some embodiments of the present application, the base film may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The base film can be a single-layer film or a multi-layer composite film, without particular limitation. When the base film is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0125] The separator membrane of the present application can be prepared by conventional methods in the art. For example, the composite material described in the first aspect of the present application can be dissolved in an organic solvent to obtain a slurry, and then the slurry is coated on the base film, and then the organic solvent is removed by drying to obtain the separator membrane of the present application.
[0126] In some embodiments of the present application, the coating density of the composite material on one side of the base film is 0.3 g / m 2 -1.0 g / m 2 , for example 0.4 g / m 2 -0.9 g / m 2 , 0.5 g / m 2 -0.8 g / m 2 , 0.6 g / m 2 -0.7 g / m 2 and so on. Thus, the adhesion between the separator membrane and the electrode can be improved, and the safety performance of the battery can be improved. In some other embodiments of the present application, the coating density of the composite material on one side of the base film can be 0.3 g / m 2 -0.8 g / m 2 .
[0127] It should be noted that the test method for the coating density of the composite material on one side of the base film: cut the separator membrane sprayed with the composite material according to the cutting template, measure the length and width of the cut sample to obtain the area S of the sample, and weigh the weight of the separator membrane sample sprayed with the composite material as M1; in the same way, cut a separator membrane sample with the same area without coating the composite material and weigh the mass as M2; the coating density of the separator membrane is (M1 - M2) / S.
[0128] The fourth aspect of the present application provides a pole piece, which includes the composite material of the first aspect above or the composite material obtained by the method of the second aspect above. Thus, cold pressing bonding between the separator and the pole piece can be achieved, and the adhesiveness between the separator and the pole piece is appropriate, thereby improving the cycle performance of the battery.
[0129] It should be noted that the pole piece described in the present application can be a positive pole piece or a negative pole piece.
[0130] The positive pole piece includes a positive current collector and a positive active material layer provided on at least one surface of the positive current collector. The positive active material layer includes the composite material of the first aspect of the present application or the composite material obtained by the method of the second aspect of the present application. Specifically, the composite material can be used as a binder in the positive active material layer.
[0131] As an example, the positive current collector has two surfaces opposite to each other in its own thickness direction, and the positive active material layer is provided on any one or both of the two opposite surfaces of the positive current collector.
[0132] In some embodiments of the present application, the positive current collector can be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil can be used. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0133] In some embodiments of the present application, the positive active material can be a positive active material for a battery well-known in the art.
[0134] As an example, when the positive pole piece is used in a lithium-ion battery, the positive active material can be a positive active material for a lithium-ion battery well-known in the art. As an example, the positive active material can include at least one of the following materials: lithium phosphate with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as the positive active material of the battery can also be used. These positive active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides can include but are not limited to lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co1 / 3Mn 1 / 3 O2 (which can also be abbreviated as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (which can also be abbreviated as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (which can also be abbreviated as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (which can also be abbreviated as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (which can also be abbreviated as NCM 811 )、lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of olivine-structured lithium-containing phosphates can include but are not limited to at least one of lithium iron phosphate (such as LiFePO4 (which can also be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate or a composite material of lithium manganese iron phosphate and carbon.
[0135] As an example, when the positive electrode sheet is used in a sodium-ion battery, the positive electrode active material can adopt the positive electrode active materials known in the art for sodium-ion batteries. As an example, the positive electrode active material can include but is not limited to at least one of layered transition metal oxides, polyanion compounds, and Prussian blue analogs.
[0136] As an example of the above-mentioned layered transition metal oxides, for example, the following can be listed:
[0137] Na 1-x Cu h Fe k Mn l M 1 m O 2-y where M 1 includes at least one of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, or Ba, 0 < x ≤ 0.33, 0 < h ≤ 0.24, 0 ≤ k ≤ 0.32, 0 < l ≤ 0.68, 0 ≤ m < 0.1, h + k + l + m = 1, 0 ≤ y < 0.2;
[0138] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2 includes at least one of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn, or Ba, and 0 < z ≤ 0.1;
[0139] Na a Li b Ni c Mn d Fe e O2, where 0.67 < a ≤ 1, 0 < b < 0.2, 0 < c < 0.3, 0.67 < d + e < 0.8, and b + c + d + e = 1.
[0140] As an example of the above polyanion compound, for example, the following can be listed:
[0141] A 1 f M 3 g (PO4) i O j X 1 3-j , where A 1 includes at least one of H, Li, Na, K, or NH4, M 3 includes at least one of Ti, Cr, Mn, Fe, Co, Ni, V, Cu, or Zn, X 1 is at least one of F, Cl, or Br, 0 < f ≤ 4, 0 < g ≤ 2, 1 ≤ i ≤ 3, 0 ≤ j ≤ 2;
[0142] Na n M 4 PO4X 2 where M 4 includes at least one of Mn, Fe, Co, Ni, Cu, or Zn, X 2 is at least one of F, Cl, or Br, 0 < n ≤ 2;
[0143] Na p M 5 q (SO4)3, where M 5 includes at least one of Mn, Fe, Co, Ni, Cu, or Zn, 0 < p ≤ 2, 0 < q ≤ 2;
[0144] Na s Mn t Fe 3-t(PO4)2(P2O7), where 0 < s ≤ 4, 0 ≤ t ≤ 3, for example, t is 0, 1, 1.5, 2, or 3.
[0145] As an example of the above Prussian blue analogues, for example, the following can be cited:
[0146] A u M 6 v [M 7 (CN)6] w ·xH2O, where A includes H + , NH4 + , at least one of an alkali metal cation or an alkaline earth metal cation, M 6 and M 7 each independently includes at least one of transition metal cations, 0 < u ≤ 2, 0 < v ≤ 1, 0 < w ≤ 1, 0 < x < 6. For example, A includes H + , Li + , Na + , K + , NH4 + , Rb + , Cs + , Fr + , Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ or Ra 2+ at least one of, M 6 and M 7 each independently includes at least a cation of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, or W.
[0147] In some embodiments, the positive electrode active material layer may further optionally include other binders. As an example, the other binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride - tetrafluoroethylene - propylene terpolymer, vinylidene fluoride - hexafluoropropylene - tetrafluoroethylene terpolymer, or tetrafluoroethylene - hexafluoropropylene copolymer and fluorinated acrylate resin.
[0148] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0149] In some embodiments, the positive electrode plate can be prepared in the following manner: the components for preparing the positive electrode plate described above, such as the positive electrode active material, the conductive agent, the composite material, and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after processes such as drying and cold pressing, the positive electrode plate can be obtained.
[0150] In some embodiments of the present application, based on the total mass of the positive electrode active material layer, the mass ratio of the composite material in the positive electrode plate is 1% - 3%, such as 1.2% - 2.8%, 1.5% - 2.5%, 1.8% - 2.2%, 2% - 2.2%, etc. Thereby, the score loss of the positive electrode plate can be reduced, and thus the cycle performance of the battery containing it can be improved.
[0151] Similarly, the electrode plate described in the present application can also be a negative electrode plate. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes the composite material described in the first aspect of the present application or the composite material obtained by the method of the second aspect of the present application. Specifically, the composite material can be used as a binder in the negative electrode active material layer.
[0152] As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is provided on any one or both of the two opposite surfaces of the negative electrode current collector.
[0153] In some embodiments of the present application, the negative electrode current collector can be a metal foil or a composite current collector. For example, as the metal foil, copper foil can be used. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0154] In some embodiments of the present application, the negative electrode active material can be the negative electrode active material for batteries well-known in the art. As an example, the negative electrode active material can include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based materials can include at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, or silicon alloys. The tin-based materials can include at least one of elemental tin, tin oxides, or tin alloys. However, the present application is not limited to these materials, and other conventional materials that can be used as the negative electrode active material of the battery can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0155] In some embodiments of the present application, the negative electrode active material layer may further optionally include other binders, and the other binders can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0156] In some embodiments of the present application, the negative electrode active material layer may further optionally include a conductive agent. The conductive agent can include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0157] In some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as thickeners (such as sodium carboxymethyl cellulose (CMC-Na)), etc.
[0158] In some embodiments of the present application, the negative electrode plate can be prepared by the following method: dispersing the components for preparing the negative electrode plate described above, such as the negative electrode active material, the conductive agent, the composite material, and any of the above optional components, in a solvent (such as deionized water) to form a negative electrode slurry; coating the negative electrode slurry on the negative electrode current collector, and after processes such as drying and cold pressing, the negative electrode plate can be obtained.
[0159] In some embodiments of the present application, based on the total mass of the negative electrode active material layer, the mass ratio of the composite material in the negative electrode plate is 1%-3%, such as 1.2%-2.8%, 1.5%-2.5%, 1.8%-2.2%, 2%-2.2%, etc. Thus, the score loss of the negative electrode plate can be reduced, thereby improving the cycle performance of the battery containing it.
[0160] In the fifth aspect of the present application, a battery is proposed, and the battery includes the separator of the third aspect described above and / or the electrode plate of the fourth aspect described above. Thus, the battery has excellent cycle performance.
[0161] Generally, a battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During the charge and discharge process of the battery, active ions are inserted into and extracted from between the positive electrode plate and the negative electrode plate. The electrolyte functions to conduct ions between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, mainly serving to prevent short circuit between the positive and negative electrodes, and at the same time allowing ions to pass through.
[0162] There is no specific limitation on the type of electrolyte in this application, and it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or all-solid-state.
[0163] In some embodiments of this application, the electrolyte uses an electrolytic solution. The electrolytic solution includes an electrolyte salt and a solvent.
[0164] In some embodiments of this application, when the battery is a lithium-ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(oxalate) borate, lithium difluoro bis(oxalate) phosphate, or lithium tetrafluorooxalate phosphate.
[0165] In some embodiments of this application, when the battery is a sodium-ion battery, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium tetrafluoroborate, sodium bis(oxalate) borate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate, or sodium bis(trifluoromethylsulfonyl)imide.
[0166] In some embodiments of this application, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, or diethyl sulfone.
[0167] In some embodiments of this application, the electrolytic solution may also optionally include additives. For example, the additives can include negative electrode film-forming additives, positive electrode film-forming additives, and can also include additives that can improve certain performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high-temperature or low-temperature performance of the battery, etc.
[0168] In some embodiments, the battery of this application includes a battery cell form, a battery module form, and a battery pack form.
[0169] In some embodiments, the positive electrode plate, the negative electrode plate, and the separator can be made into an electrode assembly by a winding process or a stacking process.
[0170] In some embodiments, the battery cell may include an outer package. The outer package may be used to encapsulate the above-mentioned electrode assembly and electrolyte.
[0171] In some embodiments, the outer package of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the battery cell may also be a soft package, such as a pouch soft package. The material of the soft package may be plastic. As plastics, polypropylene, polybutylene terephthalate, and polybutylene succinate, etc. may be cited.
[0172] This application does not particularly limit the shape of the battery cell, and it may be cylindrical, square, or any other arbitrary shape. For example, Figure 1 is a battery cell 1 with a square structure as an example.
[0173] In some embodiments, referring to Figure 2 , the outer package may include a housing 11 and a cover plate 13. Among them, the housing 11 may include a bottom plate and side plates connected to the bottom plate, and the bottom plate and the side plates enclose to form a receiving cavity. The housing 11 has an opening communicating with the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode plate, the negative electrode plate, and the separator may form an electrode assembly 12 through a winding process or a stacking process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of the electrode assemblies 12 included in the battery 1 may be one or more, and those skilled in the art can select according to specific actual needs.
[0174] In some embodiments, the battery cells may be assembled into a battery module. The number of the battery cells included in the battery module may be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0175] Figure 3 is a battery module 2 as an example. Referring to Figure 3 , in the battery module 2, a plurality of battery cells 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other arbitrary manner. Further, the plurality of battery cells 1 may be fixed by fasteners.
[0176] Optionally, the battery module 2 may further include a housing having a receiving space, and a plurality of battery cells 1 are received in the receiving space.
[0177] In some embodiments, the above-mentioned battery module may further be assembled into a battery pack. The number of the battery modules included in the battery pack may be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0178] Figure 4 andFigure 5 is a battery pack 3 as an example. Refer to Figure 4 and Figure 5 , the battery pack 1 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 can cover the lower box body 32 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0179] In addition, the present application also provides an electric device, and the electric device includes the battery provided by the present application. The battery cell, the battery module, or the battery pack can be used as the power source of the electric device or as the energy storage unit of the electric device. The electric device can include mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc., but not limited thereto.
[0180] As the electric device, the battery cell, the battery module, or the battery pack can be selected according to its usage requirements.
[0181] Figure 6 is an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for the high power and high energy density of the battery cell, a battery pack or a battery module can be adopted.
[0182] Another example of the device can be a mobile phone, a tablet computer, a laptop computer, etc. This device usually requires thin and light, and a battery cell can be used as the power source.
[0183] Hereinafter, embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application and should not be construed as a limitation to the present application. For those not specified in the embodiments regarding specific technologies or conditions, they shall be carried out according to the technologies or conditions described in the literature in the art or according to the product specifications. For the reagents or instruments not specified for the manufacturers, they are all conventional products that can be obtained through commercial purchases.
[0184] Preparation Example A1
[0185] Weigh ethyl acrylate as the first monomer, styrene as the second monomer, and acrylamide as the third monomer respectively (the mass ratio of the first monomer, the second monomer, and the third monomer is 100:15:10), and mix the monomers evenly. Add 1000 g of the mixed monomers, 30 g of sodium dodecyl sulfate emulsifier, 10 g of ammonium persulfate initiator, and 1200 g of deionized water into a 5000 mL four-necked flask equipped with a mechanical stirrer, a thermometer, and a condenser, and stir at high speed for emulsification for 30 min. Under nitrogen protection, heat up to 75 °C and react for 4 h, then cool down to below 40 °C, adjust the pH to neutral, filter and discharge to obtain acrylate polymer emulsion A1.
[0186] Preparation Examples A2 to A11, Preparation Examples A2 - A11. On the basis of Preparation Example A1, adjust the monomer types and mass ratios to obtain acrylate polymer emulsions A2 - A11, as shown in Table 1 for details.
[0187] Table 1
[0188]
[0189] Example 1
[0190] 1. Preparation of composite material
[0191] Mix acrylate polymer emulsion A1, dispersant polyvinylpyrrolidone, and polybutadiene according to a weight ratio of 100:10:30, stir evenly after mixing, and obtain the composite material through a spray drying process. The conditions of the spray drying process are an inlet air temperature of 110 °C, an outlet air temperature of 50 °C, and a wind pressure of 0.5 kPa.
[0192] 2. Preparation of separator membrane
[0193] Use a commercially available PE microporous film with a thickness of 7 μm and an average pore size of 80 nm (from Zhuogao Electronic Technology Company) as the base film. Stir and mix the above-prepared composite material evenly in deionized water to obtain a slurry (solid content is 20%). Spray the slurry on both surfaces of the base film, dry to remove the solvent, and the coating density of the coating composition on the substrate is 1.5 g / m 2 , and obtain the separator membrane.
[0194] 3. Preparation of positive electrode sheet
[0195] Mix polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), conductive agent carbon black, and N-methylpyrrolidone (NMP) according to a mass ratio of 1.2:58.38:0.42:40, and fully stir and mix evenly to prepare a positive electrode slurry. Coat the positive electrode slurry on the positive electrode current collector aluminum foil with a loading amount of 200 g / m 2 uniformly, and then after drying, cold pressing, and slitting, obtain the positive electrode sheet.
[0196] 4. Preparation of the negative electrode sheet
[0197] Artificial graphite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were added to deionized water according to a mass ratio of 96.2:1.0:1.6:1.2, and after being fully stirred and mixed evenly, a negative electrode paste (solid content of 63%) was prepared. The negative electrode paste was coated on a negative electrode current collector copper foil at a loading of 98 g / m 2 After that, it was dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0198] 5. Preparation of the electrolyte
[0199] At 25 °C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then LiPF6 was dissolved in the above-mentioned mixed solvent to obtain an electrolyte, where the concentration of LiPF6 was 1 mol / L.
[0200] 6. Preparation of the secondary battery
[0201] The above-mentioned positive electrode sheet, separator, and negative electrode sheet were stacked, wound, and cold-pressed into shape (during which the separator was bonded to the electrode sheet) to obtain an electric core; the electric core was placed in an outer package, the above-prepared electrolyte was added, and after processes such as encapsulation, standing, formation, and aging, a secondary battery was obtained.
[0202] Examples 2-26 and Comparative Examples 1-4 were obtained by adjusting the composition of acrylate polymers, dispersants, and butadiene polymers, etc. on the basis of Example 1.
[0203] Table 2
[0204]
[0205]
[0206] The particle size, Vicat softening point of the composite materials obtained in Examples 1-26 and Comparative Examples 1-4, and the cold-pressing adhesion between the electrode sheet and the separator in the obtained battery and the cycle performance of the battery were characterized, and the characterization results are shown in Table 3.
[0207] Performance testing
[0208] (1) Test of the Vicat softening point of the composite material
[0209] According to ISO 306:2013 Plastics - Determination of Vicat softening temperature of thermoplastics, test method A50 is selected. The equipment used is the WKT - VST300 thermoplastic deformation and softening point temperature tester of Jaisen Company for testing, with a load of 10 N, a heating rate of 50 °C / h, and a sample thickness of 5 mm.
[0210] (2) Particle size test of composite materials
[0211] Use a laser particle size analyzer (Malvern 3000, MasterSizer3000) for testing, and the main light source uses a helium - neon red light source. Take a clean small beaker, add 1 g of the sample to be tested, add 20 ml of deionized water, and ultrasonicate for 5 min at 53 KHz / 120 W to ensure complete dispersion of the sample. Turn on the laser particle size analyzer, clean the optical path system, and then automatically measure the background. Stir the ultrasonically treated solution to be tested to make it evenly dispersed, place it in the sample cell as required, and start measuring the particle size. The measurement result can be read from the instrument.
[0212] (3) Cold - press bonding test steps
[0213] Overlap the above - mentioned battery negative electrode plate and the separator, place them on a hot press, and set the hot press parameters as: temperature 25 °C, pressure 7 t, time 15 s, and apply pressure to obtain a bonded separator / negative electrode plate sample; cut the separator / electrode plate sample into a rectangular spline of 150 mm × 20 mm. Paste one side of the electrode of the above - mentioned rectangular spline on the steel plate with double - sided tape, and separate the separator and the electrode by 2 cm in length along the length direction at one end of the rectangular spline to prepare a test specimen.
[0214] Keep the steel plate horizontal and fix it with the lower clamp of a universal testing machine (Xieqiang Instrument Manufacturing (Shanghai) Co., Ltd., model CTM2100), fix the peeling end of the separator as described above with the upper clamp of the universal testing machine, and connect the tensile machine. Set the test conditions as a tensile rate of 20 mm / min and horizontally pull 10 cm. After the tensile force is stable, record the tensile force value, and obtain the bonding force between the separator and the electrode by the ratio of the tensile force value to the sample width.
[0215] (4) Battery cycle performance test steps
[0216] At 25 °C, charge the prepared battery at a constant current of 1 / 3C to 3.65 V, then charge it at a constant voltage of 3.65 V until the current is 0.05C, let it stand for 5 min, and then discharge it at 1 / 3C to 2.5 V. The obtained discharge capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, and at the same time record the discharge capacity C of the battery after the nth cycle n Then the battery capacity retention rate P after each cycle n =(C n((C0) / C0)×100%. That is, the difference in cycling performance can be reflected by the battery capacity retention rate after 500 cycles.
[0217] Table 3
[0218]
[0219]
[0220] As can be seen from Table 3, the composite materials of Examples 1-26 all include acrylic polymers and dispersants, and the Vicat softening point of the composite materials is between 5°C and 60°C. The cold pressing adhesion between the separator and the negative electrode sheet and the battery capacity retention rate are both higher than those of Comparative Examples 1-4. This shows that when the composite material of the present application is used for the separator, cold pressing adhesion between the separator and the electrode sheet can be achieved, and the adhesion is appropriate, thereby improving the cycling performance of the battery.
[0221] In the description of this specification, the description with reference to terms such as "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.
[0222] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present application. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present application.
Claims
1. A composite material, characterized in that, It includes acrylate polymers and a dispersant, and the Vicat softening point of the composite material is 5°C - 60°C.
2. The composite material according to claim 1, wherein The Vicat softening point of the composite material is 10°C - 50°C.
3. The composite material according to claim 1 or 2, characterized in that, The polymerization monomers of the acrylate polymers include a first monomer, a second monomer, and a third monomer. The structure of the first monomer includes: Wherein, R1 includes a hydrogen atom, a hydroxyl group, or an alkyl group with 1 - 18 carbon atoms, and R2 includes a hydrogen atom or an alkyl group with 1 - 18 carbon atoms that is substituted or unsubstituted by a hydroxyl group. The structure of the second monomer includes: Wherein, R3 and R4 each independently include a hydrogen atom, a phenyl group, or an alkyl group with 1 - 20 carbon atoms. The structure of the third monomer includes: Wherein, R5 includes a hydrogen atom or an alkyl group with 1 - 6 carbon atoms, and R6 includes a hydrogen atom, an alkyl group with 1 - 6 carbon atoms substituted by a hydroxyl group, or an alkoxy group with 1 - 6 carbon atoms.
4. The composite material according to claim 3, characterized in that, The first monomer includes at least one of ethyl acrylate, n-butyl acrylate, n-propyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isooctyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, acrylic acid, methacrylic acid, crotonic acid, or heptenoic acid.
5. The composite material according to claim 3 or 4, characterized in that, The second monomer includes at least one of styrene, pentene, hexene, heptene, octene, nonene, decene, dodecene, tridecene, tetradecene, pentadecene, or hexadecene.
6. The composite material according to any one of claims 3 - 5, wherein the third monomer includes at least one of acrylamide, methacrylamide, N-hydroxymethylacrylamide, N-butylacrylamide, N-butoxymethylacrylamide, or N-(N-butoxymethyl)acrylamide.
7. The composite material according to any one of claims 3-6, characterized in that, The mass ratio of the first monomer, the second monomer, and the third monomer is 100:(10 - 30):(1 - 20).
8. The composite material according to any one of claims 3-7, characterized in that, The mass ratio of the first monomer, the second monomer, and the third monomer is 100:(15 - 25):(5 - 15).
9. The composite material according to any one of claims 1-8, characterized in that, The mass ratio of the acrylate composite material and the dispersant is 100:(1 - 15).
10. The composite material according to any one of claims 1-9, characterized in that, The mass ratio of the acrylate composite material and the dispersant is 100:(5 - 12).
11. The composite material according to any one of claims 1 to 10, characterized in that, The dispersant includes at least one of polyvinylpyrrolidone, polyacrylamide, sodium polystyrene sulfonate, polyacrylic acid, sodium polyacrylate, or sodium polymethacrylate.
12. The composite material according to any one of claims 1-11, characterized in that, The number average molecular weight of the dispersant is 100 - 100000.
13. The composite material according to any one of claims 1-12, characterized in that, It further includes a butadiene polymer, and the butadiene polymer includes at least one of polybutadiene, styrene / butadiene copolymer, acrylonitrile / butadiene copolymer, butadiene / isoprene copolymer, or butadiene / propylene copolymer.
14. The composite material according to claim 13, characterized in that, The mass ratio of the acrylate polymer, the dispersant, and the butadiene polymer is 100:(1 - 15):(1 - 100).
15. The composite material according to claim 13 or 14, characterized in that, The mass ratio of the acrylate polymer, the dispersant and the butadiene polymer is 100:(5 - 12):(5 - 50).
16. The composite material according to any one of claims 13-15, characterized in that, The glass transition temperature of the butadiene polymer is less than or equal to 20 °C.
17. The composite material according to any one of claims 13-16, characterized in that, The Dv50 of the butadiene composite material is 100 nm - 300 nm.
18. The composite material according to any one of claims 13-17, characterized in that, The viscosity of the butadiene composite material at 25 °C is 10 mPa·s - 300 mPa·s.
19. The composite material according to any one of claims 1-18, characterized in that, The volume average particle size Dv50 of the composite material is 2 μm - 20 μm.
20. A method for preparing a composite material, characterized in that, Comprising: Mixing an acrylate polymer with a dispersant to obtain a composite material, and the Vicat softening point of the composite material is 5 °C - 60 °C.
21. An isolation film, characterized in that, Comprising the composite material according to any one of claims 1 - 19 or the composite material prepared by the method according to claim 20.
22. A pole piece, characterized in that, Comprising the composite material according to any one of claims 1 - 19 or the composite material prepared by the method according to claim 20.
23. A battery, characterized in that, Comprising the separator film according to claim 21 and / or the electrode sheet according to claim 22.
24. An electrical device, characterized in that, Comprising the battery according to claim 23.